Primaquine: A pharmaceutically active compound as corrosion inhibitor for mild steel in hydrochloric acid solution - Ahamad I.; Khan S.; Ansari K.R.; Quraishi M.A. (My University, 2025)
The corrosion inhibition of mild steel in 1 M HCl by pharmaceutically active compound, the Primaqine (PQ), was investigated by weight loss, electrochemical impedance spectroscopy (EIS) and polarization techniques. Experimental results showed that PQ is an effective inhibitor for the mild steel corrosion in 1 M HCl solutions and it exhibited >90% inhibition efficiency is >90% as low as 0.4 mM inhibitor concentration. Potentiodynamic polarization studies showed that primaquine is a mixed-type inhibitor. The results of EIS showed that PQ inhibits corrosion of mild steel by adsorption mechanism. The adsorption of inhibitor on the mild steel surface followed Langmuir adsorption isotherm. Activation energy (E a), Gibbs free energy (ΔG° ads), enthalpy (ΔH*), and entropy (ΔS*) of corrosion process were calculated and discussed.